The Privilege of Working From Home at the Time of Social Distancing - Armanda Cetrulo; Dario Guarascio; Maria Enrica Virgillito (Intereconomics, 2020)
Although the common perception is that the pandemic is `the great equaliser', workers' tasks, contractual framework and position in the internal organisational hierarchy strongly affect their ability to work remotely.
Keywords: 330